(untitled) (Vietnam Journal of Community Medicine, 2024)
Aim: (1) Survey of clinical and paraclinical characteristics of patients with popliteal artery injuries; (2) Evaluate early results after surgery to restore popliteal artery circulation at Can Tho Central General Hospital from 2021 to 2023. Methods: Retrospective descriptive study on 36 patients aged 16 years and older with popliteal artery injuries who were prescribed surgery to restore vascular circulation at the Orthopedics Trauma Center - Can Tho Central General Hospital from January 2021 until December 2023. Results: There were 36 patients with knee fractures accompanied by damage to the popliteal artery who were treated surgically to restore circulation to the popliteal artery. The average age of the research group was 29.53 ± 12.16 years old, men accounted for 77.78 %. The time from accident to surgery was recorded the most in the group ≤ 6 hours, accounting for 61.11%. Fracture location at the tibial plateau accounts for the highest proportion of popliteal artery injury cases, accounting for 63.89%. Signs of loss of contrast agent signal on CTA films accounted for 52.78%, signs of continuous loss of popliteal artery accounted for 13.89% and extravasation accounted for 33.33%. The results of limb perfusion after surgery were very good at 80.56%, good results at 11.1%, average results at 5.56%, poor results at 2.78%. Conclusion: Popliteal artery injury is a serious injury to the lower limb, leading to the patient losing lower limb function and, more seriously, death. Therefore, doctors need to diagnose early and treat properly to help save the limb and limit sequelae.